MÉTODOS MECÂNICO E QUÍMICO DE DESIDRATAÇÃO NA CONFECÇÃO DE SILAGEM PRÉ-SECADA DE AVEIA PRETA - CARNEIRO, MURILO KLOSOVSKI (2016)
The objective of this study was to evaluate the mechanical and chemical methods of dehydration in the production of pre-dried silage black oat (Avena strigosa Schreb) under different dehydration times. The experiment was conducted in an experimental design of randomized blocks with 5 repetitions, in factorial 2 x 6, 2 methods of dehydration, mechanical and chemical, on 6 dehydrating times, with 0, 3, 6, 9, 12 and 15 days after cutting or application of glyphosate herbicide. The harvest took place after 88 days after emergence, in pre-flowering stage. We evaluated the production of dry biomass at harvest, physical composition of the forage, participation in the dry matter of the plant components, loss of dry matter during dehydration to field losses during ensiling, with measurement of production effluents, as well as chemical composition of silage. There was interaction between method of dehydration x harvest time for most of the production characteristics. The chemical dehydration method showed higher recovery of dry matter to the field level. The chemical dehydration method showed no ideal DM content for pre-dried silage, however, showed greater recovery of dry matter. The longer dehydration led to lower losses in both methods of dehydration, but the chemical method did not reach MS necessary for producing quality silage, also leading to a lower quality silage.